Understanding barrier degradation during water vapour transmission rate testing of high barrier metallized paper. Issue 3 (16th December 2021) - Wyser, Yves; Vishtal, Alexey; Giardiello, Maria Isabelle; Pelletier, Chantal; Deantoni, Frédéric
Abstract: Single use packaging is one of the major contributors to environmental issues linked to waste in the environment. Packaging materials often consist of several plastics, which, when combined, are difficult to recycle. One option to reduce these issues are packaging materials for which recycling infrastructure and end markets exist, such as paper. Use of paper in food packaging applications is limited due to poor barrier properties. Enhancing barrier properties without impacting recyclability can be achieved by thin polymeric coatings combined with vapour‐deposited aluminium. Water vapour transmission rate (WVTR) of packaging materials is often assessed at 38°C and 90% relative humidity (RH). These conditions, not experienced in the supply chain, may not be optimal for paper as they have the potential to alter the structure of paper by inducing expansion disrupting barrier. This study aims at verifying this hypothesis by evaluating the influence of temperature and RH on the measured WVTR of high barrier paper. Results show that testing such papers at 38°C and 90% RH yields WVTR approximately 10 times higher than when tested at 23°C and 85% RH. The link between this increase and the disruption of the barrier layer is demonstrated by testing samples preconditioned at 38°C and 90% RH and tested at 23°C and 85% RH, depicting an increased WVTR as well. Results suggest that integrity of barrier layer in paper was disrupted at 38°C and 90% RH, and hence, these conditions are deemed inappropriate for testing barrier performance of paper materials. Abstract : This study demonstrates that measuring the water vapour transmission rate of high barrier metallized paper in accelerated conditions, for example, 38°C and 90% relative humidity, can induce hygroexpansive stresses in the metallized layer yielding to the generation of cracks and therefore erroneous values for this key property.